Intra-individual comparison of 18F-PSMA-1007 and 18F-DCFPyL PET/CT in the prospective evaluation of patients with newly diagnosed prostate carcinoma: a pilot study - Giesel, Frederik L.; Will, Leon; Kratochwil, Clemens; Haberkorn, Uwe (Journal of nuclear medicine technology, 2018)
Introduction: The introduction of 18F-labelled prostate-specific membrane antigen (PSMA) targeted positron emission tomography/computed-tomography (PET/CT) tracers, firstly 18F-DCFPyL and more recently 18F-PSMA-1007, have demonstrated promising results for the diagnostic workup of prostate cancer (PCa). This clinical study presents an intra-individual comparison to evaluate tracer-specific characteristics of 18F-DCFPyL versus 18F-PSMA-1007. Methods: Twelve prostate cancer patients, drug naive or prior to surgery, received similar activities of about 250 MBq 18F-DCFPyL and 18F-PSMA-1007 48 h apart and were imaged 2 h p.i. in the same PET/CT-scanner using the same reconstruction-algorithm. Normal organ biodistribution and tumor uptakes were quantified using SUVmax. Results: PSMA-positive lesions were detected in twelve out of twelve PCa patients. Both tracers, 18F-DCFPyL and 18F-PSMA-1007, detected the identical lesions. No statistical significance could be observed when comparing the SUVmax of 18F-DCFPyL and 18F-PSMA-1007 for local tumor, lymph node metastases and bone metastases. With regard to normal organs, 18F-DCFPyL presented statistically significant higher uptake in kidneys, urinary bladder and lacrimal gland. Vice versa, significantly higher uptake of 18F-PSMA-1007 in muscle, submandibular and sublingual gland, spleen, pancreas, liver and gallbladder was observed. Conclusion: Excellent imaging quality was achieved with both 18F-DCFPyL and 18F-PSMA-1007 resulting in identical clinical findings for the evaluated routine situations. Non-urinary excretion of 18F-PSMA-1007 might present some advantage with regard to delineation of local recurrence or pelvic lymph-node metastasis in selective patients; the lower hepatic background might favor 18F-DCFPyL in very late stages when rare cases of liver metastases can occur.
Published online: December 21, 2017
Im Titel falsche Schreibweise von Uwe Haberkorn
Im Titel ist "18" hochgestellt
Gesehen am 21.06.2018